False negative results in luminex panel reactive antibody identification assay: Should we be alert on them? (Annals of Medical Research, 2021)
Aim: Panel Reactive Antibodies (PRA) analysis is important not only in virtual cross-match of donors and recipients but also in follow-up of recipients immune response after transplantation. Although bead based tests give faster and more reliable, it may have false positive and negative results. We investigated HLA groups of patients with false negative results and the frequencies of anti-HLA antibodies in all three false negative situations.Materials and Methods: PRA results of all patients were divided into 3 groups according to negative controls and samples results. First one is negative controls were false negative and samples were false negative (1st Situation); second one is negative controls were false negative but samples were true negative (2nd Situation); third one is negative controls were true negative but samples were false negative (3rd Situation). All serum samples were tested by bead based Luminex assay.Results: While anti-HLA-A68, A24, A32 were the most frequent antibodies for the first situation, anti-HLA-A03,24,32 were the most frequent three antibodies for the second situation. In case of anti-HLA-B antibodies; anti-HLA-B38, B44, B48 were detected for the first situation, and anti-HLA-B44, B58, B49 were detected for the second situation. In case of class II antibodies; we detected anti-HLA-DRB110, DRB115 and DRB151 antibodies as the most frequent three antibodies at 1st situation. Frequencies of anti-HLA antibodies of 120 patients with false negative results were determined in serum samples. In case of 3rd situation, while anti-A23, A68, A24; anti-B06, B04, B39 and anti-Cw07 were the most frequent anti-HLA Class I antibodies, anti-HLA DQ07, DQ05, DQ04 and anti-HLA-DRB152, DRB113, DRB153 were the most frequent HLA-Class II antibodies detected in serum samples.Conclusion: Samples with false negative PRA results should be repeated and these samples should be recorded in the laboratory for internal control system.
Keywords: Bead Assay; HLA; PRA analysis